Bibliometric and visual analyses of vaccine literacy research from 1982 to 2023 - Jingzhi Wang; Yazhou Wang; Yuanheng Li; Mingxue Ma; Yuzhuo Xie; Yuwei Zhang; Jiaqi Guo; Jiajun Shi; Chao Sun; Haoyu Chi; Hanye Tang; Vsevolod Ermakov; et al. (Human Vaccines & Immunotherapeutics)
Vaccine literacy (VL) is an important part of health literacy (HL), which is of great significance in reducing vaccine hesitancy and improving vaccine coverage rate. We aimed to perform a bibliometric analysis of VL research conducted from 1982 to 2023 to evaluate its current status and prospects. All relevant publications were retrieved from the Web of Science Core Collection database and the Scopus database. The Bibliometrix R-package and VOSviewer software were used to analyze the publication outputs, countries, organizations, authors, journals, cited publications, and keywords. In total, 1,612 publications were included. The number of articles published on VL generally showed an increasing trend. The United States was in a leading position among all countries and had the closest connections with other countries and organizations. Its in-depth study of vaccine hesitancy provided a good foundation for VL research. Harvard University was the most productive organization. Bonaccorsi G was the most productive and cited author. VACCINES was the most productive journal. Research topics primarily revolved around vaccination, HL, vaccine hesitancy, and COVID-19 vaccine. In conclusion, the current research on the conceptual connotation and influencing factors of VL is insufficiently deep and should be further improved in the future to distinguish it from HL in a deeper manner. More tools for measuring VL need to be developed, such as those applicable to different populations and vaccines. The more complex relationship between VL, vaccine hesitancy and vaccination needs to be further explored. Gender differences deserve further investigation.